Perception Of Students On The Apple Smartphone As A Lifestyle: Persepsi Mahasiswa Terhadap Smartphone Apple Sebagai Gaya Hidup - Vivi Mulyati; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the perception of communication science students towards the Apple Smartphone brand as a lifestyle. This study uses the theory of Jean Boudrillard. Data collection was carried out by means of in-depth interviews and observations, supported by relevant literature by focusing on communication science students at the Muhammadiyah Sidoarjo university. The method used is purposive sampling, this technique uses informants who have been determined or have predetermined criteria to support this research. The results of the discussion above can be concluded that students' perceptions of smartphones as a lifestyle are divided into the following processes, one, perceptual selection occurs when students remember that iPhone users will look more visible or high-class than other smartphone users, and make users more confident. Second, the student perception organization collects information from various sources to be understood in order to consider whether to buy or not, so that they will not be disappointed with the items they buy. Third, the interpretation of the stimulus describes the meaning of the Apple smartphone as a brand that provides an identity for its users.